Single and dual target inhibitors based on Bcl-2: Promising anti-tumor agents for cancer therapy - Liu, Tingting; Wu, Zhongyu; He, Yujing; Xiao, Yuliang; Xia, Chengcai (European journal of medicinal chemistry, 2020)
B-cell lymphoma-2 (Bcl-2) proteins family is an essential checkpoint in apoptosis. Extensive evidences suggested that overexpression of anti-apoptotic Bcl-2 proteins can be observed in multiple cancer cell lines and primary tumor biopsy samples, which is an important reason for tumor cells to evade apoptosis and further acquire drug resistance for chemotherapy. Hence, down-regulation of anti-apoptotic Bcl-2 proteins is effective for the treatment of cancers. In view that Bcl-2 inhibitors and some other anti-tumor agents, such as HDAC inhibitors and Mdm2 inhibitors, exert synergy effects in tumor cells, it is pointed out that dual-targeting therapies based on these targets are regarded as rational strategies to enhance the effectiveness of single target agents for cancer treatment. This review briefly introduces the apoptosis, the structure of Bcl-2 family proteins, and focuses on the current status and recent advances of Bcl-2 inhibitors and the corresponding SARs of them. Moreover, we discuss the synergisms between Bcl-2 and other anti-tumor targets, and summarize the current dual-target agents. [Display omitted] •Inhibition of Bcl-2 has been an effective strategy for cancer treatment.•Dual-target inhibitors based on Bcl-2 as anti-cancer agents, such as Bcl-2/HDAC dual inhibitors, and single-target agents were summarized.•We made an insight into the structure-activity relationships of these agents.•We summarize the synergistic mechanisms and effects of Bcl-2 based dual-target inhibitors.